The Effect of Employee Experience and Engagement on Intention to Leave with Innovative Work Behavior as a Mediating Variable - Mashanafi, Dwi Pratiktho; Putranta, Martinus Parnawa (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
The purpose of this study is to analyze the effect of employee experience and employee engagement on intention to leave through innovative work behavior as a mediating variable using a sample of 168 employees who worked in startup digital companies in Indonesia. Purposive sampling was used to invite respondent participation. Structual Equation Modelling was employed for data analysis. Then the result shows that employee experience and employee engagement had a direct and negative effect on intention to leave, while employee engagement is not proven to have a direct effect on intention to leave. Innovative work behavior also succesfully fully mediated the relationship between employee engagement and intention to leave.